Kolonisasi Politik dalam Kebijakan Inovasi Pemerintahan Daerah - Noor, Irwan; Riyanto, Riyanto; Wahyudi, Lestari Eko (Jurnal Ilmiah Administrasi Publik, 2021)
The question posed in this research is "Do political institutions participate in producing products and carry out various influences on innovation policies?" This study contributes to understanding the role of politics in innovation policies in local government. This research was conducted in two areas, namely Malang City and Malang Regency. The method used is available data analysis (secondary data). There are 4 focus studies that are examined. There are two analyzes used in this study, namely: First, the data obtained secondary to descriptive analysis was carried out with Excel, then further analyzed using SmartPLS for inference analysis. The findings of this study reveal that the political environment has a negative relationship with both innovation achievements and local government performance. However, in elaboration on policies, it turns out that political colonization occurs in policy products. This research also reveals why innovative areas are never sustainable in terms of their innovation achievements. Although this research can reveal policy colonization by the political environment, the limitations of the scope of the research area, and the scale used to limit this research. For this reason, it is advisable for a more detailed study by expanding and comparing the regions, both those interpreted in the IGA and TOP 99, and those that are not.